Money, financial stability and efficiency - Allen,F; Carletti,E; Gale,D (Journal of Economic Theory, 2014)
Most analyses of banking crises assume that banks use real contracts but in practice contracts are nominal. We consider a standard banking model with aggregate return risk, aggregate liquidity risk and idiosyncratic liquidity shocks. With non-contingent nominal deposit contracts, a decentralized banking system can achieve the first-best efficient allocation if the central bank accommodates the demands of the private sector for fiat money. Price level variations allow full sharing of aggregate risks. An interbank market allows the sharing of idiosyncratic liquidity risk. In contrast, idiosyncratic (bank-specific) return risks cannot be shared using monetary policy alone as real transfers are needed.